ASSESSMENT OF THE READINESS OF UKRAINIAN ENTERPRISES TO TAKE INTO ACCOUNT ESG FACTORS WHEN PLANNING BUSINESS STRATEGIES - YATSYSHYNA, Klavdiia; YATSYSHYN, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The question of sustainability has long been an integral part of the DNA and development strategy of any size enterprise. Sustainability is a set of enterprise initiatives based on its values, such as initiatives related to the implementation of the UN's 17 Sustainable Development Goals, environmental activities, and corporate social responsibility. In the general concept of "sustainable development goals," there is primarily a vector on which the top management of the enterprise or any other business entity can orientate in the development of a strategy. In contrast, ESG is a component of the entire business environment and includes three fundamental pillars of the strategy: environmental, social, and governance sustainability. ESG is always a hidden part that shows the potential of the enterprise to both management and investors. Today, compliance with ESG principles becomes not only a requirement of regulators and international financial organizations but also a desire of management and business owners. But is there a correlation between ESG programs and the financial results that the enterprise demonstrates? According to the results of the KPMG study "Business Leaders' View in Ukraine 2021," almost half of the leaders of Ukrainian enterprises see an increasing demand from stakeholders for the introduction of ESG principles into their business strategies. However, only 14% of executives believe that their ESG programs improve financial results. In the world, this figure is four times higher - 52%. Nevertheless, the topic of ESG has turned the world, thinking, and approach to doing business upside down.
Keywords: sustainable development; ESG factors; climate neutrality; decarbonization; stakeholders; ESG reporting